Mixed convection flow near a non-orthogonal stagnation point towards a stretching vertical plate - Lok, Yian Yian (Elsevier B.V., 2007)
An analysis of the steady two-dimensional mixed convection flow of an incompressible viscous fluid near an oblique stagnation point on a heated or cooled stretching vertical flat plate has been studied. It is assumed that the plate is stretched with a velocity proportional to the distance from a fixed point and the temperature of the plate is constant. Both the cases of the assisting and opposing flows are considered. It is shown that the velocity increases as the shear parameter Î³ increases with the increase of the straining parameter a/c. These flows have a boundary layer structure near the stagnation region. It is also found that the flow has an inverted boundary layer structure when the stretching velocity of the surface exceeds the stagnation velocity of the free stream (a/c < 1). It is shown that the position of the point xs of zero skin friction (shear stress on the wall) is shifted to the left or to the right of the origin and it depends upon the balance between obliqueness, straining motion and buoyancy effects